If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + -4) = 3x + -24 Reorder the terms: 6(-4 + x) = 3x + -24 (-4 * 6 + x * 6) = 3x + -24 (-24 + 6x) = 3x + -24 Reorder the terms: -24 + 6x = -24 + 3x Add '24' to each side of the equation. -24 + 24 + 6x = -24 + 24 + 3x Combine like terms: -24 + 24 = 0 0 + 6x = -24 + 24 + 3x 6x = -24 + 24 + 3x Combine like terms: -24 + 24 = 0 6x = 0 + 3x 6x = 3x Solving 6x = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 6x + -3x = 3x + -3x Combine like terms: 6x + -3x = 3x 3x = 3x + -3x Combine like terms: 3x + -3x = 0 3x = 0 Divide each side by '3'. x = 0 Simplifying x = 0
| 40.5p+14.40=4.50(p+3) | | 20+10x=4x-40 | | 10m+(-1)=12 | | y+34=-15 | | 6x-2=6x-54 | | 2y=x-x/2 | | 7/10=x/6 | | 10m+(-2)=12 | | 5x^2-32x-469=0 | | 1/7x^2-x+11/5=0 | | -3(k+4)+k=-16 | | 7/8x=10 | | -23x+32=-5+57x | | 6b6/3b3 | | -16-(-6x)=6x+2 | | 10x-5=7x+9 | | x+1=-15+5x | | D=9/8(m-57) | | 3(2x+1)=3x-5 | | 4.5z-2.5z=25 | | 20+10x=10x-20 | | y=230+2x-0.5x^2 | | 20x+50=12-7x | | 4-6x+7x=16 | | 2/5(x-5)=6 | | 8n+34=32+8n | | (5y-4)(3+y)=0 | | 3g-3+7=3g+4 | | -4(2x-4)=-8x+16 | | 9x+3=-4(-2x-10) | | Y/3+4=-16 | | .99s=10+.89s |